Gestão holística do tempo: o potencial de utilização do Sincronário das 13 luas na gestão estratégica de negócios e projetos criativos - Costa, Lucas Silva da (2023)
With the arrival of the New Economies, especially the Creative Economy, new management models have been required. These new models must take into account the current socio-environmental context in which our society finds itself and adopt characteristics such as greater creativity, flexibility and self-management in its organizational processes. However, a key factor still needs to be better investigated within organizational management, time. This study aimed to evaluate the potential use of a time management tool, the 13 Luas Sincronário, in the creative management of projects and organizations. To develop this study, an Action Research was carried out, where a Holistic Model for Creative Project Management, derived from the 13 Luas Synchrony, was created and evaluated. This model brings as potential benefits a tool capable of contributing to human self-development, a synergy between the participants of a project, in addition to facilitating the emergence of a feeling of connection with nature